2022
DOI: 10.1126/sciadv.abo2295
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-mediated stabilization of HIF1A in prostatic intraepithelial neoplasia promotes cell plasticity and malignant progression

Abstract: Prostate cancer (PCa) is a leading cause of cancer-related deaths. The slow evolution of precancerous lesions to malignant tumors provides a broad time frame for preventing PCa. To characterize prostatic intraepithelial neoplasia (PIN) progression, we conducted longitudinal studies on Pten (i)pe−/− mice that recapitulate prostate carcinogenesis in humans. We found that early PINs are hypoxic and that hypoxia-inducible factor 1 alpha (HIF1A) signaling is activated in luminal cells, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…35 Under the effects of HIF-1α, prostate intraepithelial neoplasia (PIN) cells highly express transglutaminase 2 (TGM2) and exhibit impaired androgen signaling, enhancing malignant progression. 23 In addition, some factors, such as Orai1; 134 phospholipase D2 (PLD2); 135 annexin A3 (ANXA3); 136 CXCR4; 137 cysteine-rich protein 2 (CSRP2); 138 hematopoietic pre-B cell leukemia transcription factor-interacting protein (HPIP); 139 twist family bHLH transcription factor 2 (TWIST2); 140 and noncoding RNAs, such as long-stranded non-coding RNA (lncRNA) PVT1, 141 lncRNA-GAPLINC, 142 and LncRNA-MTA2TR; 143 and micro-RNAs, such as miR-525-5p, 144 miR-301a-3p, 145,146 and miR-141-3p, 147 play important roles in regulating hypoxia-induced cancer cell proliferation, migration, invasion, and angiogenesis in the TME under hypoxic conditions (Table 1).…”
Section: Hypoxia Signaling Pathways and Cancer Cells Hifs And Cancer ...mentioning
confidence: 99%
See 1 more Smart Citation
“…35 Under the effects of HIF-1α, prostate intraepithelial neoplasia (PIN) cells highly express transglutaminase 2 (TGM2) and exhibit impaired androgen signaling, enhancing malignant progression. 23 In addition, some factors, such as Orai1; 134 phospholipase D2 (PLD2); 135 annexin A3 (ANXA3); 136 CXCR4; 137 cysteine-rich protein 2 (CSRP2); 138 hematopoietic pre-B cell leukemia transcription factor-interacting protein (HPIP); 139 twist family bHLH transcription factor 2 (TWIST2); 140 and noncoding RNAs, such as long-stranded non-coding RNA (lncRNA) PVT1, 141 lncRNA-GAPLINC, 142 and LncRNA-MTA2TR; 143 and micro-RNAs, such as miR-525-5p, 144 miR-301a-3p, 145,146 and miR-141-3p, 147 play important roles in regulating hypoxia-induced cancer cell proliferation, migration, invasion, and angiogenesis in the TME under hypoxic conditions (Table 1).…”
Section: Hypoxia Signaling Pathways and Cancer Cells Hifs And Cancer ...mentioning
confidence: 99%
“…[19][20][21][22] Intra-tumor hypoxia is linked to decreased disease-free survival outcomes in several cancers including prostate, cervical cancer, and head and neck squamous cell carcinoma (HNSCC). [23][24][25][26] The hypoxic environment alters the expression levels of genes that modulate metabolism and other processes. Moreover, hypoxic signaling interacts with other cellular pathways to alter cancer cell malignant behaviors and is closely associated with cancer cell proliferation, migration, invasion and angiogenesis, and affects cancer treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting these results, in Pten Knockout PCa mouse models, the expression level of the glycolytic enzymes has been recently reported to be associated with the expression of luminal hypoxia-inducible factor 1 alpha (HIF-1α), and the expression of EZH2 and SOX2 in advanced stages of tumoral development. Moreover, luminal HIF-1α promotes the elevation of MDSCs-recruiting factors [ 249 ]. In addition, the metabolic reprograming in tumoral cells also involves lipid and amino acid metabolism [ 250 , 251 ], and in PCa, it has been shown that EZH2 is involved in the alteration of multiple metabolic pathways (reviewed in [ 250 ]).…”
Section: Role Of Ezh2 In Tumoral Metabolismmentioning
confidence: 99%
“…We have previously shown that prostatic intraepithelial neoplasia (PIN) of Pten (i)pe−/− mice, generated by luminal epithelial cell‐specific deletion of the tumor suppressor PTEN after puberty, is hypoxic and that enhanced hypoxia‐inducible factor 1 (HIF1) signaling in luminal cells drives the malignant evolution of such lesions (Abu El Maaty et al , 2022 ). In this study, we analyzed the molecular underpinnings enabling luminal cell survival in tumors of Pten (i)pe−/− mice under androgen deprivation conditions and found that castration resistance is associated with further activation of hypoxic signaling and a shift in luminal cell state.…”
Section: Introductionmentioning
confidence: 99%